Kiswahili Verbs: A Lexicographical Challenge - Mochiwa, Z.s.m. (Lexikos, 2007)
Abstract: This article makes three significant claims about Kiswahili verbs. By investigating the verbal root pend- 'love' the article claims that the agglutinative nature of Bantu languages is at the core of the morphological fecundity of Kiswahili verbs. Evidenced both vertically and horizontally, the fecundity brings in, respectively, extensions and derivations. The article claims further that each of the extensions of the verb can, theoretically at least, participate in derivational processes. The second claim is that this fecundity triggers lexicographical problems of choice and semantic analysis. Specifically, the article underscores the need for selectivity of information to control the density of the dictionary entry. Yet, selectivity presupposes a thorough analysis of the morphosyntactic behaviour of the verb in its many extended and derived forms. Indeed, such an analysis presupposes, in turn, an eclectic use of many linguistic theories. Bantu lexicography must be up front in making theoretically sound decisions. Finally, on the basis of linguistic theories, lexicography becomes a concretization of the mental lexicon claimed to be part of the competence of the native speaker.Keywords: KISWAHILI, VERBS, LEXICOGRAPHY, LEXICON, DICTIONARY, INFLEC-TION, EXTENSION, DERIVATION, CAUSATIVE, SOUND-MEANING, ROOT, CITATIONOpsomming: Kiswahiliwerkwoorde: 'n Leksikografiese uitdaging. Hierdie artikel maak drie betekenisvolle bewerings oor Kiswahiliwerkwoorde. Deur 'n ondersoek van die verbale kern pend- "liefhê" beweer die artikel dat die agglutinerende aard van die Bantoetale aan die kern lê van die morfologiese vrugbaarheid van Kiswahiliwerkwoorde. Soos sowel vertikaal as horisontaal getoon, lei die vrugbaarheid tot suffiksering en afleiding onderskeidelik. Die artikel beweer verder dat elk van die agtervoegsels van die werkwood, teoreties altans, aan die afleidings-prosesse kan deelneem. Die tweede bewering is dat hierdie vrugbaarheid leksikografiese probleme van keuse en semantiese ontleding veroorsaak. Die artikel onderstreep veral die noodsaaklikheid van die selektiwiteit van inligting om die digtheid van die woordeboekinskrywing te beheer. Se-lektiwiteit veronderstel egter 'n deeglike ontleding van die morfosintaktiese gedrag van die werk-woord in sy talle gesuffikseerde en afgeleide vorme. Op sy beurt veronderstel so 'n ontleding inderdaad 'n eklektiese gebruik van talle taalkundige teorieë. Bantoeleksikografie moet die eerste wees in die maak van teoreties gegronde besluite. Op grond van linguistiese teorieë word die lek-sikografie uiteindelik 'n konkretisering van die mentale leksikon wat na bewering deel van die vermoë van die moedertaalspreker is.Sleutelwoorde: KISWAHILIWERKWOORDE, LEKSIKOGRAFIE, LEKSIKON, WOORDE-BOEK, VERBUIGING, SUFFIKSERING, OORSAAKLIK, KLANK-BETEKENIS, KERN, AANHA-LING